2001
DOI: 10.1007/s004250100604
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and biochemical characterization of a heteromeric protein phosphatase 2A holoenzyme from maize ( Zea mays L.) leaves that dephosphorylates C 4 phospho enol pyruvate carboxylase

Abstract: The activity and allosteric properties of plant phosphoenolpyruvate carboxylase (PEPC; EC 4.1.1.31) are controlled posttranslationally by specific reversible phosphorylation of a strictly conserved serine residue near the N-terminus. This up/down-regulation of PEPC is catalyzed by a dedicated and highly regulated serine/threonine (Ser/Thr) kinase (PEPC-kinase) and an opposing type-2A Ser/Thr phosphatase (PP2A). In marked contrast to PEPC-kinase, the PP2A holoenzyme from photosynthetic tissue has been virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…3). One might not expect to see close coupling between mRNA levels and the PEPC phosphorylation state because the PEPC phosphorylation level is determined by the balance of the PEPC-PK activity and the protein phosphatase activity (Dong et al, 2001). Therefore, reduction of the PEPC-PK mRNA level strongly supports our thesis that low PEPC phosphorylation in these transgenic plants is due to reduced levels of PEPC-PK.…”
Section: Relationship Between Pepc Phosphorylation and Leaf Metabolitsupporting
confidence: 68%
See 1 more Smart Citation
“…3). One might not expect to see close coupling between mRNA levels and the PEPC phosphorylation state because the PEPC phosphorylation level is determined by the balance of the PEPC-PK activity and the protein phosphatase activity (Dong et al, 2001). Therefore, reduction of the PEPC-PK mRNA level strongly supports our thesis that low PEPC phosphorylation in these transgenic plants is due to reduced levels of PEPC-PK.…”
Section: Relationship Between Pepc Phosphorylation and Leaf Metabolitsupporting
confidence: 68%
“…Phosphorylation of C 4 -PEPC at its conserved Ser residue near the N terminus is thought to be controlled primarily by the light-dependent activity of a protein kinase specific to PEPC (PEPC-PK) because the activity of the protein phosphatase 2A involved in PEPC dephosphorylation appears to be constant under various conditions (Vidal and Chollet, 1997;Dong et al, 2001;Nimmo, 2003;Izui et al, 2004). Recently, cDNA clones for PEPC-PK have been cloned and characterized in vitro for a number of species (Izui et al, 2004;Shenton et al, 2006); in particular, Tsuchida et al (2001) have cloned and characterized the expression of PEPC-PK from Flaveria trinervia.…”
mentioning
confidence: 99%
“…Interestingly, this lowabundance PEPC kinase is degraded by the proteasome after polyubiquitination, but the E3 ligase is not yet known (Agetsuma et al, 2005). An unidentified phosphatase (Protein phosphatase 2A family) dephosphorylates PEPC in darkness, thereby down-regulating PEPC activity (Dong et al, 2001;Izui et al, 2004). The regulation of this phosphatase is still unknown.…”
Section: (Classic) Examples Of Plant Metabolic Enzymes and Pathways Rmentioning
confidence: 99%
“…A considerable number of biochemical, pharmacological, and genetic studies have shown that PP2A is involved in the control of constitutive plant processes, such as cell cycle, metabolism, ion channel fluxes, growth and development, pollination and seed germination, and in the defense against many biotic or abiotic challenges (Smith and Walker, 1996;Luan, 2003;DeLong, 2006). PP2A has been proposed to modulate several metabolic processes in vascular plants, including sucrose synthesis, quinate metabolism, nitrogen assimilation, and nocturnal CO 2 fixation (Siegl et al, 1990;MacKintosh et al, 1991;MacKintosh, 1992;Dong et al, 2001), but its involvement in isoprenoid biosynthesis had not been established. The broad distribution and functional diversity likely correspond to a multiplicity of PP2A holoenzymes (each formed by one A, one B-type, and one C subunit) reflected at the genomic level.…”
Section: Hmgr Pp2a and The Signal Transduction Networkmentioning
confidence: 99%